2018
DOI: 10.3390/su10020473
|View full text |Cite
|
Sign up to set email alerts
|

Food Access and Coping Strategies Adopted by Households to Fight Hunger among Indigenous Communities of Sierra Tarahumara in Mexico

Abstract: Households' food access remains a concern primarily in rural households in lower-and middle-income countries. The purpose of this study is to measure food access and to identify the coping strategies in indigenous households of the communities of Sierra Tarahumara in Mexico. The representative sample was made up of 123 households from 38 communities. The survey was conducted face to face during the winter season between February and March 2015. Since all respondents only speak the Tarahumara language, authors … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 28 publications
1
15
0
Order By: Relevance
“…Another study among indigenous communities of Sierra Tarahumara in Mexico found that skipping meals was the most frequent coping strategy (56.10 percent), followed by restricted consumption by adults so that small children can eat (52.85 percent) and limited portion size at mealtimes (49.59 percent). This study also found that 5.69 percent of the households would gather wild food, hunt, or harvest immature crops while they faced food insecurity[22]. Supporting our results, a study in rural households in upland areas, Sekong province in Laos, found that gathering wild foods was the most common coping strategy used by households.…”
Section: Discussionsupporting
confidence: 85%
“…Another study among indigenous communities of Sierra Tarahumara in Mexico found that skipping meals was the most frequent coping strategy (56.10 percent), followed by restricted consumption by adults so that small children can eat (52.85 percent) and limited portion size at mealtimes (49.59 percent). This study also found that 5.69 percent of the households would gather wild food, hunt, or harvest immature crops while they faced food insecurity[22]. Supporting our results, a study in rural households in upland areas, Sekong province in Laos, found that gathering wild foods was the most common coping strategy used by households.…”
Section: Discussionsupporting
confidence: 85%
“…In Ethiopia, a 40–70 % price increment was documented for nutritious food commodities like eggs, meat, dairy and other products since the year of 2005 (55) . Studies from Jimma in Ethiopia (56) and Sierra Tarahumara in Mexico (57) identified households’ shifting to inexpensive food items as a coping strategy for food insecurity. This could explain the inverse association between household food insecurity and ASF consumption frequencies observed in the present study districts.…”
Section: Discussionmentioning
confidence: 99%
“…Economic variables (income, expenditure, and BDH program), as independent variables, alone do not explain food insecurity since there are also social, demographic, and environmental variables that can explain food insecurity in the estimation of a model. Consequently, there are some studies that analyze the association between dependent and independent variables of the common determinants of food insecurity, which include individual, household, and socioeconomic characteristics [2,14,15,33,34,40,57].…”
Section: Discussionmentioning
confidence: 99%